Virtual reality in assessment and treatment of schizophrenia: a systematic review - Macedo,Mônica (2015)
Objective To conduct a systematic review about the use of virtual reality (VR) for evaluation, treatment and/or rehabilitation of patients with schizophrenia, focused on: areas, fields and objectives; methodological issues; features of the VR used; viability and efficiency of this resource. Methods Searches were performed about schizophrenia and virtual reality in PsycINFO, Academic Search Complete, MEDLINE Complete, CINAHL with Full Text, Web of Science and Business Source Premier databases, using the following keywords: [“schizophrenia”] AND [“virtual reality” OR “serious game”] AND [“treatment” OR “therapy” OR “rehabilitation”]. The search was carried out between November 2013 and June 2014 without using any search limiters. Results A total of 101 papers were identified, and after the application of exclusion criteria, 33 papers remained. The studies analysed focused on the use of VR for the evaluation of cognitive, social, perceptual and sensory skills, and the vast majority were experimental studies, with virtual reality specifically created for them. All the reviewed papers point towards a reliable and safe use of VR for evaluating and treating cognitive and social deficits in patients with schizophrenia, with different results in terms of generalisation, motivation, assertiveness and task participation rate. Some problems were highlighted, such as its high cost and a constant need for software maintenance. Conclusion The studies show that using the virtual reality may streamline traditional evaluation/rehabilitation programmes, allowing to enhance the results achieved, both in the cognitive and in the social field, helping for the legitimisation of this population’s psycho-social inclusion.